The Antifungal Effect of Essential Oils of Curcuma mangga Rhizomes on Candida albicans Growth In Vitro - Khairunnisa, Afifah Syifa; Haryati, Sri; Setyawan, Sigit (Nexus Biomedika, 2017)
Background: Candida albicans is a normal flora that can be turned into a pathogen on an immunocompromised person. Candida sp. infection, or commonly referred to candidiasis, can be treated with azole group such as fluconazole. Fluconazole has some side effects like gastrointestinal disorders, urticarial rash, and eosinophilia. The fluconazole-resistant Candida albicans has also been reported several times, so future research about antifungal substance is needed. Curcuma manggaâs essential oils contain some substances which has antifungal effect (caryophyllene, caryophyllene oxide, Î²-pinene). The objective of this study is to know the antifungal effect of essential oil of Curcuma mangga rhizomes on Candida albicans growth in vitro. Methods: The study was quasi experimental laboratory with post test only group design study and have been performed in Parasitology Laboratory Faculty of Medicine, Sebelas Maret University, Surakarta. The subject of this study was Candida albicans taken from clinical sample with random sampling. Curcuma manggaâs essential oils which used in this study were diluted with ethanol 70% into various concentrations (1,5%, 2%, 2,5%, 3%, 3,5%). Subject was inoculated on Sabboraud Dextrose Agar (SDA) media with 6 mm diametric well, filled with each type of essential oil concentration. Inhibition zone diameter as the data was analyzed using Kruskal Wallis and Mann Whitney statistical test. Result: The antifungal effect of 2,5% until 3% concentration of Curcuma mangga rhizomeâs essential oilsÂ equals with the antifungal effect of ketoconazole 25Âµg/mL and in 3,5% concentration ofÂ Curcuma mangga rhizomeâs essential oils exceed the antifungal effect of ketoconazole 25Âµg/mL. Conclusions: Essential oils of Curcuma mangga rhizomes have antifungal effect on Candida albicans growth in vitro. Keywords: Curcuma mangga Val., essential oils, Candida albicansÂ